PERAN FALSAFAH TRI HITA KARANA BAGI PERTUMBUHAN DAN KINERJA LEMBAGA PERKREDITAN DESA (LPD) DI BALI - Ketut Gunawan (Jurnal Analisis Manajemen, 2011)
One of the institutions of micro economy in Bali is Lembaga Perkreditan Desa (LPD) which is owned by the village. LPD in Bali has the anually average of assets development about 24,55%, the average of fund development in a form of saving and deposit about 25,11%, and credits about 23,84%, credits problem volume about 1,98 % and Capital Adequati Ratio about 25 %. Its means LPD has a Good Performance and Growth. Hindus in Bali follow the value of balance which based on the theory of Tri Hita Karana which consists of : Parahyangan, Pawongan, and Palemahan. By writing this paper, the writer wants to explain the theory of Tri Hita Karana and the performance and Growth of LPD in Bali. The purposes are : first, to understand the general background of LPD in Bali; second, to understand the values which exist in the theory of Tri Hita Karana; third, to know the role of the theory of Tri Hita Karana for the Performance and Growth of LPD in Bali. The result of this study shows that : first, LPD as the important place of many sacred values in Bali has excellent of Performance and Growth; second, there are many sacred and high values exist in the theory of Tri Hita Karana, they are : always stay in Gods path, honesty, hardworking, excellent time management, harmonious cooperation, faith in words, efficiency, full of creativeness and spirit to grow more, keeping the safety. Third, the values of Tri Hita Karana can form the good mentality of the stakeholders of LPD which has been playing the important role to developing and Performance the LPD in Bali.